2018
DOI: 10.1039/c8ra07912a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acylation and glycation treatments on physicochemical and gelation properties of rapeseed protein isolate

Abstract: Acylated and glycated RPI gels were prepared, but the moderate acylation was more favorable to improve the gelation property of RPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The secondary protein structures were mainly composed of β‐sheet (at 1615–1640 cm −1 and 1689–1698 cm −1 region), β‐turn (at 1660–1688 cm −1 region), α‐helix (1650–1659 cm −1 region), random coil (1641–1649 cm −1 region) (Wang et al., 2018). The proportion of the secondary structure of MOSSP is presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The secondary protein structures were mainly composed of β‐sheet (at 1615–1640 cm −1 and 1689–1698 cm −1 region), β‐turn (at 1660–1688 cm −1 region), α‐helix (1650–1659 cm −1 region), random coil (1641–1649 cm −1 region) (Wang et al., 2018). The proportion of the secondary structure of MOSSP is presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The EAI and ESI reached their maximum values at an SA/SPI mass ratio of 15% with 52.58 m 2 g −1 and 121.84 min respectively. The reason for this change might be attributed to the unfolding of the secondary conformation of the protein during the succinylation treatment; that is, the reduction of the β ‐sheet content and the increase in the random coil content 50 . Meanwhile, an enhancement of protein flexibility affected the protein–lipid interaction and the structural rearrangement of the proteins at the oil–water interface, promoting protein diffusion at the oil–water interface and the formation of interfacial films around the emulsion droplets 27 .…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this change might be attributed to the unfolding of the secondary conformation of the protein during the succinylation treatment; that is, the reduction of the ⊎-sheet content and the increase in the random coil content. 50 Meanwhile, an enhancement of protein flexibility affected the protein-lipid interaction and the structural rearrangement of the proteins at the oil-water interface, promoting protein diffusion at the oil-water interface and the formation of interfacial films around the emulsion droplets. 27 Generally, flexible proteins have better emulsification properties and, conversely, rigid proteins have poor emulsification properties.…”
Section: Interfacial Functional Properties Analysis Emulsifying Prope...mentioning
confidence: 99%
“…Therefore, how glycation and glycation parameters would have affected the total solubility was quite significant. In the literature, it was reported that glycation could enhance the solubility of a protein because the pH of the environment during the reaction may lead to structural changes such as disruption of large aggregates, which increase the protein solubility (Wang et al ., 2018). Furthermore, with the addition of reducing sugars in the reaction, a well‐dispersed aqueous phase with a more hydrophilic environment may occur, and this inhibits the aggregation of the proteins, thereby enhancing the interaction with the aqueous phase (Wen et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%